Comparison of Renal Functional Status after Percutaneous Nephrolithotomy with Single and Multiple Tract Accesses - Khan, AKM Fazlay Rabbi; Asaduzzaman, Muhammad; Rahman , Mahmud Ur; Hasan, Mohammad Tanvir; Gupta, Sudip Das; Majumder, Sharif Muhammad Mahmudul Hasan Majumder; Farhana, Fatima (Journal of Comilla Medical College Teachers’ Association, 2025)
Background: Percutaneous nephrolithotomy is the preferred treatment for patients with large complex stones. More than one percutaneous access may be required for stone clearance, potentially increasing the risk of renal injury. Objective: This study is aimed to compare the renal functional status after percutaneous nephrolithotomy (PCNL) with single and multiple tract accesses. Methodology: This prospective quasi experimental study was conducted in the Department of Urology, Sir Salimullah Medical College Mitford Hospital, Dhaka during the period of January 2019 to December 2020. Total 42 renal calculi patients were included by a predefined inclusion and exclusion criteria and allocated into two groups with equal distribution. Patients of Group-A and Group-B underwent single tract PCNL and multiple tract PCNL respectively. Results: Result: On the 2nd post-operative day, both Group A and Group B showed a significant rise in serum creatinine and a decline in eGFR compared to preoperative values (p < 0.05), though inter-group differences were not significant (p > 0.05). By the third post-operative month, serum creatinine and eGFR values returned to baseline in both groups, with no significant intra- or inter-group differences (p > 0.05). DTPA renogram with GFR of the affected kidney at the third month also showed no significant changes from preoperative values or between groups (p > 0.05). Conclusion: Based on the study findings inference can be drawn that there is no significant renal functional changes are observed after percutaneous nephrolithotomy between single or multiple access tracts. J Com Med Col Teachers’ Asso July 2025; 29(2): 133-138